2006
DOI: 10.1002/dvdy.20897
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of gene expression inXenopushindlimbs during stage‐dependent complete and incomplete regeneration

Abstract: Xenopus laevis tadpoles are capable of limb regeneration after amputation, in a process that initially involves the formation of a blastema. However, Xenopus has full regenerative capacity only through premetamorphic stages. We have used the Affymetrix Xenopus laevis Genome Genechip microarray to perform a large-scale screen of gene expression in the regeneration-complete, stage 53 (st53), and regeneration-incomplete, stage 57 (st57), hindlimbs at 1 and 5 days postamputation. Through an exhaustive reannotation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 76 publications
6
73
0
Order By: Relevance
“…Taking this example then, one could predict that either regeneration is entirely controlled by reactivation of developmental mechanisms, or that the triggers that drive the choice between regeneration and wound healing vary between different tissues. One of these genes, Xnlrr-1, was also identified by Grow et al in their limb screen, as differentially expressed in st. 53 limbs at 1 and 5 days after amputation (Grow et al, 2006). Grow et al also identified several other genes in common with the Tazaki list (Grow et al, 2006).…”
Section: Can We Identify Common Mechanisms and Genes?mentioning
confidence: 99%
See 3 more Smart Citations
“…Taking this example then, one could predict that either regeneration is entirely controlled by reactivation of developmental mechanisms, or that the triggers that drive the choice between regeneration and wound healing vary between different tissues. One of these genes, Xnlrr-1, was also identified by Grow et al in their limb screen, as differentially expressed in st. 53 limbs at 1 and 5 days after amputation (Grow et al, 2006). Grow et al also identified several other genes in common with the Tazaki list (Grow et al, 2006).…”
Section: Can We Identify Common Mechanisms and Genes?mentioning
confidence: 99%
“…However, the approaches used were rather different. Grow et al (2006) compared the transcriptome of regeneration competent (st. 53) and incompetent (st. 57) limb after 1 or 5 days of regeneration. Pearl et al (2008) compared st. 52 regenerating limbs to those blocked by transgenic expression of the Bmp inhibitor Noggin, 3 days after amputation.…”
Section: Microarray Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also the rationale behind the new global bioinformatic and systems biology approaches that integrate the molecular elements of large genomic and proteomic databases into functional networks and pathways from which hypotheses about mechanisms emerge (Nabel, 2009). For example, global genomic and proteomic data on blastema formation in regenerating anuran and urodele limbs has been generated by a number of laboratories Habermann et al, 2004;Putta et al, 2004;Grow et al, 2006;Pearl et al, 2008;Smith et al, 2009;Monaghan et al, 2009;Rao et al, 2009) and in one case transcription factor pathways have been subjected to a systems biology analysis (Jhamb et al, 2011).…”
Section: New Approaches and Challengesmentioning
confidence: 99%